2015
DOI: 10.5603/fm.2015.0007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of liquid diet on the parotid gland and the protective role of L-carnitine: immunohistochemical and ultrastructural study

Abstract: (Folia Morphol 2015; 74, 1: 42-49)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Moreover, El Gharmawy (2015) explained that the main organelles affected by oxidative stress were mitochondria and endoplasmic reticulum as a result of depriving the cell of energy production [47] . Saggu et al (2010) reported similar changes in the sequence of cell apoptosis [48] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, El Gharmawy (2015) explained that the main organelles affected by oxidative stress were mitochondria and endoplasmic reticulum as a result of depriving the cell of energy production [47] . Saggu et al (2010) reported similar changes in the sequence of cell apoptosis [48] .…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that children with eating difficulties resulting from enteral or parenteral nutrition in neonatal periods have a lower antioxidant status (146): however, supplementation of a liquid diet with L-carnitine in rat prevented atrophy of the parotid glands. L-carnitine has been hypothesized to protect the mitochondria and endoplasmic reticulum from oxidative stress that results from decreased cellular energy production (147). Being a potential scavenger of ROS, L-carnitine is an antioxidant that prevents the impairment of fatty acid oxidation in the mitochondria.…”
Section: No + O −mentioning
confidence: 99%
“…There was a significant decrease in the mean area percent stained with PAS in the parotid gland of the hyperlipidemic group as compared to control group. This may be due to decreased ability of the gland to synthesize zymogen granules with diminished secretory activity of amylase exerted by degenerated acini leaving empty secretory granules that react weakly with PAS stain [34] .…”
Section: Discussionmentioning
confidence: 99%